The Effectiveness of Using Narrative Approach in Teaching the Course of Interpretation (Tafseer) in Developing the First Intermediate Female Students’ Conceptual Understanding (Journal of the College of Education for Women, 2021)
This study aims at examining the effectiveness of using the narrative approach in teaching the Interpretation of the Qur'an course in the development of conceptual comprehension among first-grade middle school female students. To achieve the objective of this study, a quantitative quasi-experimental design has been used. The sample consisted of first-grade middle school female students at "the third middle school" in Buraidah city, as this school suits the objective of the study. A test of conceptual understanding has been built by the researchers according to a list of conceptual understating skills at a significance level of α ≤ 0.05. Results have shown that there are statistically significant differences at the level (α ≤ 0,05) between the mean scores of the experimental group and the control group students regarding the conceptual comprehension test in favour of the experimental group. Moreover, there are statistically significant differences between the mean scores of the experimental group students in the pre- and post-conceptual comprehension tests in favour of the post-test. Based on these results, the researchers have provided a set of related recommendations and suggestions, such as: accentuating the importance of using the narrative approach in constructing Sharia sciences courses in general and the interpretation of the Qur'an course in particular. Accordingly, the researchers have recommended conducting a study entitled the effectiveness of using the narrative approach in teaching the interpretation of the Qur'an course in developing the first-grade secondary school students’ conceptual comprehension.